Desenvolvimento de um sensor de baixo custo e descartável para o monitoramento de odor - Hayashi, Roberto Kenji (Universidade Federal de São Carlos, 2015)
The research proposal was found low cost alternative solution to automatize the classification and selection process to recognize fruit ripeness level using biologic behavior instead of human visual inspection. The goal was to develop low cost and disposable solid state sensor made of office paper with respective equipment for odor monitoring. The concept used to development this sensor was replace the interdigitated electrode with a conductive track using office paper impregnated with an electrolyte that "turns" cellulose fiber in an electrical conductor under gas action. In order to get gas adsorbing surface property for odor monitoring were tested some electrolytes like: Magnesium Chloride, Potassium Iodide, Calcium Hydroxide and others. This configuration replaced the interdigitated electrode per cellulose fiber doped with an electrolyte, it´s the originality of this research. In the fruit ripening process, the major enzymes involved are pectinase to crack the cell walls responsible for the fruits softening, amylase which degrades carbohydrates to simple sugars responsible for the flavor and hydrolase which reduces the amount of chlorophyll responsible for the fruit color change. The reaction that produces ethylene gas (C2H4) is lipids oxidation, the main gas exhaled during the fruits ripening process. The equipment adopted to pick up electrical signal is based on resistance and capacitance measuring that showed reversible electrical signal variation basically due the track geometry and cellulose fiber doping with an electrolyte. Another feature found was the office paper sensor decrease resistivity with fruit odors presence. The sensor manufacturing process is simple, basically consist in printing a mask with a negative image of the track by laser printing and office paper impregnation by an electrolyte.
Keywords: Sensor de estado sólido; Sensor de baixo custo; Sensor descartável; Sensor de odor banana; Nariz eletrônico; Low cost sensor; Disposable sensor; Banana´s odor sensor; Office paper sensor; Fruit ripeness sensor; Solid state sensor; e-Nose; CIENCIAS BIOLOGICAS::BIOQUIMICA